Preserving Memory Documenting and Archiving Latin American Human Rights - Llamas, Nerea A. (Seminar on the Acquisition of Latin American Library Materials, 2013)
Selected papers from the annual conference of the Seminar on the Acquisition of Latin American Library Materials